(3SjQ CYdGe GdfHdGAs - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s
(3ChdgG (B:s
(3CHh YHjO I Hf GdLQGM YGeQ Hf YHO Gddg CMO GdSGHbjf GdChdjf hef YRe GdUOjb Ydi JhdjJg GdNdGaI hGTGQ Hg jhe GdSbjaI dceGd CgdjJg YfO CHj HcQ s
(3BNQgG (B:s
(3bGd (B: (3aeG cfJ CQjO JeQkG EdG CONdJ jOi Je GdLRA GdKGdK ef cJGH SjQ CYdGe GdfHdGA s
(3GdeNWhW YHGQI Yf cJGH eWHhY bGe HJMbjbI OcJhQ UdGM GdOjf GdefLO hCNQLg eYgO GdeNWhWGJ GdYQHjI HGdETJQGc eY OGQ GdeYGQa HeUQs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1015s
Keywords: (3GdJGQjNs